RGB-Colored Cu(In,Ga)(S,Se)(2) Thin-Film Solar Cells with Minimal Efficiency Loss Using Narrow-Bandwidth Stopband Nano-Multilayered Filters - Lee, Soyoung; Yoo, Gang Yeol; Kim, Byungwoo; Kim, Min Kyu; Kim, Changwook; Park, Sang Yeun; Yoon, Hee Chang; Kim, Woong; Min, Byoung Koun; Do, Young Rag (American Chemical Society, 2019)
Colorful Cu(In,Ga)(S,Se)(2) (CIGSSe) thin-film solar cells were achieved by integrating a narrow-bandwidth stopband filter (NBSF) on a CIGSSe cell. The full range of visible color of NBSF could be realized by depositing one-dimensional nano-multilayers of alternating high-index (Al2O3) and low-index (SiO2) films while controlling the thickness of each layer and the number of stacked layers. Particularly, high-purity red, green, and blue (RGB) colors were generated on black CIGSSe cells with minimal harvest efficiency drop, showing power conversion efficiency (PCE) losses for the red and green CIGSSe cells of 4.2 and 1.2%, respectively, with no reduction in the PCE of the blue CIGSSe cell. The minimal drop in the harvest efficiency was attributed to the antireflection effect of the NBSF and the low overlap between the reflectance spectrum of NBSFs with a narrow stopband and the absorption spectrum of CIGSSe. The esthetic value could be further enhanced through the color variation of the RGB NBSF with viewing angle, so-called pearl-like colors. The synergetic effect of minimal efficiency loss, full color realization, and the pearl-like color change of the newly developed NBSFs can make CIGSSe cells applicable to building-integrated photovoltaics.
Keywords: POWER-CONVERSION EFFICIENCY; PHOTONIC CRYSTALS; ENERGY-STORAGE; WHITE-LIGHT; LAYER; MANAGEMENT; WINDOW; CHALCOPYRITE; PHOSPHOR